Studi Literatur: Keefektifan Teknik Quantum Reading dalam Mengoptimalkan Kecepatan Membaca dan Pemahaman Teks pada Siswa Sekolah Dasar - Latifah Mihar; Indah Surya Hasari; M Habibi (STKIP Subang, 2026)
The low level of reading literacy among elementary school students remains a major challenge in the learning process, particularly due to the use of less varied instructional methods and limited active student engagement. This study aims to comprehensively examine the effectiveness of the Quantum Reading technique in optimizing reading speed and text comprehension among elementary school students. The study employed a systematic literature review method by analyzing indexed journal articles published between 2016 and 2026. Based on the PRISMA flow, 59 articles were initially identified, and 10 articles met the inclusion criteria for further analysis. The findings reveal that the Quantum Reading technique consistently improves students’ reading speed without reducing their level of reading comprehension and, in many cases, enhances both simultaneously. These improvements are supported by the implementation of strategies such as the use of visual pointers, the expansion of visual span, and positive psychological conditioning, enabling students to become more focused and comfortable while reading. In addition, this method has been proven to increase students’ reading interest, active participation, and reduce cognitive fatigue during the learning process. Therefore, Quantum Reading can be considered an innovative and effective approach that is worthy of implementation in elementary school reading instruction. The findings of this study imply that teachers need adequate understanding and training to optimally integrate the Quantum Reading technique in order to improve students’ literacy quality.